Mucoadhesive Pharmacology: Latest Clinical Technology in Antiseptic Gels - María Baus-Domínguez; Felipe-Rodrigo Aguilera; Fernando Vivancos-Cuadras; Lourdes Ferra-Domingo; Daniel Torres-Lagares; José-Luis Gutiérrez-Pérez; Tanya Pereira-Riveros; Teresa Vinuesa; María-Ángeles Serrera-Figallo (Gels, 2023)
Chlorhexidine (CHX) is one of the most widely used antiseptics in the oral cavity due to its high antimicrobial potential. However, many authors have stated that the effect of CHX in nonsurgical periodontal therapy is hampered by its rapid elimination from the oral environment. The aim of this study was to determine the antibacterial efficacy of a new compound of chlorhexidine 0.20% + cymenol (CYM) 0.10% on a multispecies biofilm. For this, an in vitro study was designed using a multispecies biofilm model of Streptococcus mutans, Fusobacterium nucleatum, Prevotella intermedia, and Porphyromonas gingivalis. Quantification of the microbial viability of the biofilm was performed using 5-cyano-2,3-ditolyl tetrazolium-chloride (CTC) to calculate the percentage of survival, and the biofilms were observed using a a confocal laser scanning microscopy (CLSM). It was observed that the bactericidal activity of the CHX + cymenol bioadhesive gel was superior to that of the CHX bioadhesive gel, in addition to higher penetrability into the biofilm. Therefore, there was greater elimination of bacterial biofilm with the new compound of chlorhexidine 0.2% plus cymenol 0.1% in a bioadhesive gel form compared to the formulation with only chlorhexidine 0.2% in a bioadhesive gel form.